Sol-gel synthesis and characterization of ZnAl2O4 powders for transparent ceramics. Issue 4 (March 2019) - Belyaev, A.V.; Lelet, M.I.; Kirillova, N.I.; Khamaletdinova, N.M.; Boldin, M.S.; Murashov, A.A.; Balabanov, S.S.
Abstract: The sol-gel synthesis of ZnAl2 O4 ceramic powders from alkoxide and acetate sources of metals, as well as the microstucture and the hardness of the hot-pressed ZnAl2 O4 specimens were considered. ZnAl2 O4 powders were prepared by the hydrolysis of an alcohol solution of aluminium isopropoxide using an aqueous solution of zinc acetate followed by heat treatment. The thermal evolution of the ZnAl2 O4 precursor was investigated. The effect of calcination temperature on the morphology and the specific surface area of ZnAl2 O4 powders were also studied. The sintering of the resultant powders to the high transparent ceramic using a hot pressing with 1 wt% ZnF2, as a sintering additive was successfully demonstrated. The in-line transmittance of ZnAl2 O4 ceramics (1 mm thickness) achieved 80% in the visible region and 85% at 5 µm; Vickers hardness was 11.6 GPa.